Is the Fundamental Theory Necessary? Remarks on the David Chalmers' Theory of Consciousness - Hohol, Mateusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
The article presents a survey of the fundamental theory of consciousness according to David Chalmers. In order to examine these issues the following actions are taken. In the first part, the philosophical and cognitive-scientific views of David Chalmers are summarized in detail. Particular attention is paid to the following issues: the distinction between the easy and hard problem of consciousness, the nature of qualia, supervenience, as well as the arguments against the reductive accounts of consciousness. The elements of the structure of Chalmers’ fundamental theory: e.g., the principle of structural coherence, the principle of organizational invariance and the principle of double aspects of information are presented. Also, the problems of the relationship between mind and quantum mechanics are analyzed. In the second part, Chalmers’ theory of consciousness is challenged and criticized in three areas: cognitive science, philosophy of science and philosophy of physics. In the summary, the reply to the question in the title of the article is suggested.